2021
DOI: 10.12890/2021_002769
|View full text |Cite
|
Sign up to set email alerts
|

Post-mRNA COVID-19 Vaccination Myocarditis

Abstract: A new trend of myocarditis among young adults who received mRNA vaccines for COVID-19 is emerging. We present the case of a young adult who presented with chest pain 3 days after the second dose of Pfizer-BioNTech COVID-19 vaccine. He had elevated troponin I and C-reactive protein levels at the time of admission. Electrocardiogram (ECG) and echocardiogram findings were unremarkable. The patient improved with conservative management and was discharged home the next day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Subsequently, 10 studies were excluded for the following reasons: inclusion of pediatric cases (n=7) [20] , [21] , [22] , [23] , [24] , [25] , [26] , diagnosis of multisystem inflammatory syndrome (n=1) [27] , analysis of incidence data of a pharmacovigilance database (n=1) [28] and opinion paper (n=1) [29] . Therefore, 39 studies were included; 37 of them [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] provided individual data of 86 participants, forming the pooled cohort. On the other hand, 2 observational studies [67] , [68] reported aggregated data of 43 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 10 studies were excluded for the following reasons: inclusion of pediatric cases (n=7) [20] , [21] , [22] , [23] , [24] , [25] , [26] , diagnosis of multisystem inflammatory syndrome (n=1) [27] , analysis of incidence data of a pharmacovigilance database (n=1) [28] and opinion paper (n=1) [29] . Therefore, 39 studies were included; 37 of them [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] provided individual data of 86 participants, forming the pooled cohort. On the other hand, 2 observational studies [67] , [68] reported aggregated data of 43 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , …”
Section: Resultsmentioning
confidence: 99%
“…We identified 201 studies relevant to COVID‐19 vaccination and myocarditis. Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis 8–65 . A total of 275 cases of COVID‐19 vaccine‐associated myocarditis were reported.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 268 potentially relevant articles from which 75 unique studies involving 188 patients met eligibility criteria [ 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Resultsmentioning
confidence: 99%